Lettergraphy. Synthesis and Visual Communication - Osnaya Baltierra, Santiago (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
Letters appeared in the world as a necessity for communication. They were created as images which represented ideas and sounds. Through time letters were transformed into what people now know as an alphabet. Today this language system seems to be invisible, probably because of the everyday with which it is manipulated. In this sense the objective of the text is to propose a semantic distancing from the conventional use of letters to state that through the form and expressiveness of each letter it is possible to transmit a message.